Pacific identities and well-being : cross-cultural perspectives - Agee, Margaret Nelson (New York : Routledge, 2013)
"Filling a significant gap in the cross-cultural and cross-disciplinary literature within the field of Pasifika (Polynesian) and Maori identities and mental health, this volume focuses on bridging mental health related research and practice within the indigenous communities of the South Pacific. Much of the content reflects both differences from and relationships with the dominant Western theories and practices so often unsuccessfully applied with these groups. The contributors represent both experienced researchers and practitioners and address topics such as research examining traditional and emerging Pasifika identities; contemporary research and practice in working with Pasifika youth and adolescents; culturally-appropriate approaches for working with Pasifika adults; and practices in supervision that have been developed by Maori and Pasifika practitioners. Chapters include practice scenarios, research reports, analyses of topical issues, and discussions about the appropriateness of applying Western theory in other cultural contexts. As Pasifika cultures are still primarily oral cultures, the works of several leading Maori and Pasifika poets that give voice to the changing identities and contemporary challenges within Pacific communities are also included"--
pt. I. Identity -- pt. II. Therapeutic practice -- pt. III. Death and dying -- pt. IV. Reflexive practice.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Pacific Islanders -- New Zealand -- Mental health; Cross-cultural counseling; Psychotherapy; Pacific Islanders -- New Zealand -- Ethnic identity; Electronic books